Physical activity among patients with diabetes mellitus in primary healthcare centers from Lima Norte - Morales, Juan (2018)
Objectives: To determine the level of physical activity in patients with type 2 diabetes mellitus who received medical attention in primary health care in North Lima. Materials and methods: This was a cross-sectional descriptive study in 164 patients of both genders, aged between 23 and 64 years, with a diagnosis of type 2 diabetes mellitus. The evaluation of physical activity was carried out with the short version of the International Physical Activity Questionnaire (IPAQ). Results: We included 164 patients with a mean age of 51.3 years (SD = 8.5), 61% (n = 100) were women, 64.6% (n=106) with ages ≥50 years, 63.4% (n=104) had secondary education, 59.8% (n=98) had been diagnosed 2 to 5 years ago. Regarding the level of physical activity, in 20.7% (n = 34) it was low, 53.7% (n = 88) moderate and 25.6% (n = 42) high. Low level of physical activity was predominant in patients ≥50 years (p = 0.001) and in those with a primary education level (p=0.008). Patients with shorter time of diagnosis of the disease showed greater tendency to perform physical activity (p = 0.004). The greatest source of physical activity was obtained in the activity "walk". Moderate physical activity occurred mainly in males (p<0.001). Conclusions. Patients with DM2 predominantly perform physical activity of moderate and low intensity, which reveals that they present minimal level of physical activity or are inactive.